FLIGHT RISKS: EXPLORING AIRCRAFT COLLISIONS WITH BIRDS OF PREY (ORDERS FALCONIFORMES AND ACCIPITRIFORMES) (International Journal of Food and Nutritional Sciences, 2022)
We examine statistical data on aircraft collisions with Accipitriformes and Falconiformes, two families of birds of prey. The analysis was based on research conducted at the Russian Academy of Sciences' Severtsov Institute of Ecology and Evolution (IPEE RAS). Predator birds' motivations and attractive elements to airfields are examined. Seven prey bird species involved in 29 airplane crashes between 2005 and 2022 were identified. The common buzzard, Buteo buteo, and the common kestrel, Falco tinnunculus, are the species with the highest frequency of bird attacks. The majority of crashes happen at the airport or close by; takeoff strikes happen 4.3 times more often than landing strikes. Crashing into raptors mostly damages the engine or the wing structure. Controlling bird behavior is advised in order to reduce the number of prey-bird collisions at the airport.